REPRESENTASI FEMINISME DAN IMPIAN HIDUP DAMAI TIONGKOK: STUDI TINDAK TUTUR ASERTIF DAN IMPLIKATUR KONVENSIONAL - Vincensius, David (Paramasastra : Jurnal Ilmiah Bahasa Sastra dan Pembelajarannya, 2023)
The Chinese government as one of the influential countries for world development also participates in efforts to protect equal women’s rights and peace life realization. This was heard in the Chinese government’s speech to the United Nations on October 1, 2020. This study aims to discuss the contents of the speech which represents the actions of feminism and dream of peace life by China by applying the theory of assertive speech acts and conventional implicatures to provide new understanding and knowledge related to real social issues developing now. Through this research, it can be seen that in the speech text, there are 3 purposes of assertive speech acts, namely 5 data to state, 4 data to claim, and 1 data to conclude. Each of these objectives has implicatures resulting from document studies supported by speech and news data that are realized in linguistic and social contexts. The stated goals are that China has actively voiced gender equality through the Beijing World Conferences on Women since 1995, is concerned about women’s work, the existence of women is very influential in the 21st century, will always fight for women’s rights, and long for an equal society. The purpose of the claim is that China claims the existence of women to create peace, oversees the progressive development of the existence of women’s rights, guarantees women’s protection rights, and that the country is an active country in voicing gender equality. The purpose of the conclusion is that China concludes that Chinese women love their country and are willing to fight for the safety of their people regardless of differences. The results of this study provide a description that China is now a country that struggles to protect women and yearns for a peace life.